RESULTS OF THE STUDY ON THE PROCESS OF SELF- ACTUALIZATION AMONG ADOLESCENTS - Saipova Malaxat, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation.  The  process  of  self-actualization  in  a  teenager’s  personality  is complicated  by  age-related  characteristics.  In  this  context,  the  author,  within  the framework of his research, focused on the course of this process in adolescents growing up in families affected by labor migration. He also drew his own conclusions based on the research results presented in the table and diagram.